Issues for Irish alcohol policy: a historical perspective with some lessons for the future - McCoy, Daniel A. (Statistical and Social Inquiry Society of Ireland, 1992)
It is not the intention of this paper to propose what the national alcohol policy should contain but rather to raise the level of debate on the crucial issues that need to be addressed. The format of the paper is as follows. Section 2 outlines from a historical context the issues that a national alcohol policy would need to address. Section 3 examines the trends in alcohol production, distribution and consumption. Section 4 describes the types and extent of alcohol related problems. Section 5 examines the etiological factors that influence drinking patterns. Section 6 examines some of the more frequently proposed methods of controlling alcohol in society and Section 7 contains some concluding remarks.
Read before the Society, 24 October 1991
Keywords: Alcohol consumption; Anti-social behaviour; 314.15